Pulse parameter optimizer: an efficient tool for achieving prescribed dose and dose rate with electron FLASH platforms - Jain, S; Cetnar, A; Woollard, J; Gupta, N; Blakaj, D; Chakravarti, A; Ayan, A S (Physics in medicine & biology, 2023)
Purpose . Commercial electron FLASH platforms deliver ultra-high dose rate doses at discrete combinations of pulse parameters including pulse width (PW), pulse repetition frequency (PRF) and number of pulses ( N ), which dictate unique combinations of dose and dose rates. Additionally, collimation, source to surface distance, and airgaps also vary the dose per pulse (DPP). Currently, obtaining pulse parameters for the desired dose and dose rate is a cumbersome manual process involving creating, updating, and looking up values in large spreadsheets for every treatment configuration. This work presents a pulse parameter optimizer application to match intended dose and dose rate precisely and efficiently. Methods . Dose and dose rate calculation methods have been described for a commercial electron FLASH platform. A constrained optimization for the dose and dose rate cost function was modelled as a mixed integer problem in MATLAB (The MathWorks Inc., Version9.13.0 R2022b, Natick, Massachusetts). The beam and machine data required for the application were acquired using GafChromic film and alternating current current transformers (ACCTs). Variables for optimization included DPP for every collimator, PW and PRF measured using ACCT and airgap factors. Results . Using PW, PRF, N and airgap factors as parameters, a software was created to optimize dose and dose rate, reaching the closest match if exact dose and dose rates are not achievable. Optimization took 20 s or less to converge to results. This software was validated for accuracy of dose calculation and precision in matching prescribed dose and dose rate. Conclusion . A pulse parameter optimization application was built for a commercial electron FLASH platform to increase efficiency in dose, dose rate, and pulse parameter prescription process. Automating this process reduces safety concerns associated with manual look up and calculation of these parameters, especially when many subjects at different doses and dose rates are to be safely managed.